Green synthesis of MgO nanoparticles and its antibacterial properties - Rotti, Rajeshwari B.; Sunitha, D. V.; Manjunath, Ramya; Roy, Arpita; Mayegowda, Shilpa Borehalli; Gnanaprakash, A. P.; Alghamdi, Saad; Almehmadi, Mazen; Abdulaziz, Osama; Allahyani, Mamdouh; Aljuaid, Abdulelah; Alsaiari, Ahad Amer; et al. (Frontiers in Chemistry, 2023)
Magnesium oxide nanostructured particles (NP) were prepared using a simple solution combustion technique using different leaf extracts such as Mangifera indica (Mango - Ma), Azadirachta indica (Neem—Ne), and Carica papaya (Papaya—Pa) as surfactants. The highly crystalline phase of MgO nanostructures was confirmed by PXRD and FTIR studies for 2 h 500°C calcined samples. To analyze the characteristics of obtained material–MaNP, NeNP, and PaNP for dosimetry applications, thermoluminescence (TL) studies were carried out for Co-60 gamma rays irradiated samples in the dose range 10–50 KGy; PaNP and NeNP exhibited well-defined glow curve when compared with MaNP samples. In addition, it was observed that the TL intensity decreases, with increase in gamma dose and the glow peak temperature is shifted towards the higher temperature with the increase in heating rate. The glow peak was segregated using glow curve deconvolution and thermal cleaning method. Kinetic parameters estimated using Chen’s method, trap depth (E), and frequency factor (s) were found to be 0.699, 7.408, 0.4929, and 38.71, 11.008, and 10.71 for PaNP, NeNP, and MaNP respectively. The well-resolved glow curve, good linear behavior in the dose range of 10–50, KGy, and less fading were observed in PaNP as compared with MaNP and NeNP. Further, the antibacterial activity was checked against human pathogens such as Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. A visible zone of clearance was observed at 200 and 100 μg/mL by the PaNP and NeNP, indicating the death of colonies by the nanoparticles. Therefore, PaNP nanomaterial is a potential phosphor material for dosimetry and antibacterial application compared to NeNP and MaNP.